GE_GERICHTE C/311/2016 vom 28. November 2016 - GE Cour de justice (2016)
DIVORCE ; ACTION EN MODIFICATION ; MESURE PROVISIONNELLE ; OBLIGATION D'ENTRETIEN ; ENFANT ; ÉCOLAGE ; INSTRUCTION(ENSEIGNEMENT) | CPC.261; CC.302.2;